Generic, specific and direct object of a crime under the Article 330 of the Criminal Code of Ukraine - V. Yu. Boichuk (Bulletin of Kharkiv National University of Internal Affairs)
The author has carried out the research of one of the mandatory elements of corpus delicti under the Art. 330 of the Criminal Code of Ukraine – its object. In the course of its analysis, the author has considered general classification of objects of a crime generally adopted in the doctrine of criminal law of Ukraine (depending on the degree of generalization of the social relations protected by the criminal law, which are the objects of various crimes) into general, generic, specific and direct ones. The concept and essence of general, generic, specific and direct objects of a crime under the Art. 330 of the Criminal Code of Ukraine, are determined on the basis of views on the object from the standpoint of the theory of social relations.